The relevance of Latin American women architects regarding Ricardo Palma’s story «La protectora y la libertadora» («The Protector and the Liberator») - Ortiz Curinambe, Abigail Eunice (2023)
In the story «La protectora y la libertadora», by Ricardo Palma, Doña Rosa Campusano, and Doña Manuela Sáenz are important characters for the independence of Latin America. Although both are considered transcendental figures in the events of their time, the former is described as a lady of refined delicacy and singular sweetness; while the latter is characterized as a «mistake of nature» with «manly aspirations». From this symbolic antagonism between the figure of the protector and the liberator, this article will focus on demystifying the prejudices about women in our society, especially in Latin America, where they are in a position of cultural segregation compared to Western Europe. The main objective of this article is to make this problem visible and propose solutions to combat gender injustice in the field of architecture in our country. The situation of women in history will be analyzed. The socioeconomic problem which affects the material conditions of children and youngers who are potential Peruvian architects will be examined. It will also present examples of empowered women architects who challenged the undervaluation of women in the construction sector, and who demonstrated that female capacity is not limited to housework nor is it inferior to male capacity in any form. A list of the great female masters of Latin American architecture with international recognition will be compiled; and, finally, the perspective of important Peruvian women architects who contribute to architecture from different approaches will be presented: Tania Cerrón, as an important architect of great influence in sustainable construction with bamboo in Peru, and Lourdes Giusti, as dean of the College of Architects of Peru.